The interleukin-1 receptor type-1 in disturbed flow-induced endothelial mesenchymal activation - Kidder, Evan; Pea, Meleah; Cheng, Siyuan; Koppada, Satya-Priya; Visvanathan, Suren; Henderson, Quartina; Thuzar, Moe; Yu, Xiuping; Alfaidi, Mabruka (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis is a progressive disease that develops in areas of disturbed flow (d-flow). Progressive atherosclerosis is characterized by bulky plaques rich in mesenchymal cells and high-grade inflammation that can rupture leading to sudden cardiac death or acute myocardial infarction. In response to d-flow, endothelial cells acquire a mesenchymal phenotype through endothelial-to-mesenchymal transition (EndMT). However, the signaling intermediaries that link d-flow to EndMT are incompletely understood. In this study we found that in human atherosclerosis, cells expressing SNAI1 (Snail 1, EndMT transcription factor) were highly expressed within the endothelial cell (EC) layer and in the pre-necrotic areas in unstable lesions, whereas stable lesions did not show any SNAI1 positive cells, suggesting a role for EndMT in lesion instability. The interleukin-1 (IL-1), which signals through the type-I IL-1 receptor (IL-1R1), has been implicated in plaque instability and linked to EndMT formation in vitro. Interestingly, we observed an association between SNAI1 and IL-1R1 within ECs in the unstable lesions. To establish the causal relationship between EndMT and IL-1R1 expression, we next examined IL-1R1 levels in our Cre-lox endothelial-specific lineage tracing mice. IL-1R1 and Snail1 were highly expressed in ECs under atheroprone compared to athero-protective areas, and oscillatory shear stress (OSS) increased IL-1R1 protein and mRNA levels in vitro. Exposure of ECs to OSS resulted in loss of their EC markers and higher induction of EndMT markers. By contrast, genetic silencing of IL-1R1 significantly reduced the expression of EndMT markers and Snail1 nuclear translocation, suggesting a direct role for IL-1R1 in d-flow-induced EndMT. In vivo, re-analysis of scRNA-seq datasets in carotid artery exposed to d-flow confirmed the IL-1R1 upregulation among EndMT population, and in our partial carotid ligation model of d-flow, endothelial cell specific IL-1R1 KO significantly reduced SNAI1 expression. Global inhibition of IL-1 signaling in atherosclerosis as a therapeutic target has recently been tested in the completed CANTOS trial, with promising results. However, the data on IL-1R1 signaling in different vascular cell-types are inconsistent. Herein, we show endothelial IL-1R1 as a novel mechanosensitive receptor that couples d-flow to IL-1 signaling in EndMT